Characterisation of a monolithic ΔE-E diamond telescope detector using low energy ion microbeams. (December 2022) - Verona, C.; Parisi, G.; Cesaroni, S.; Crnjac, A.; Jakšić, M.; Marinelli, M.; Palomba, S.; Romano, F.; Schettino, G.; Verona Rinati, G.
Abstract: Telescope detectors have long been studied for their capability of discriminating the type of radiation detected. Silicon is the most widely used material for solid-state detectors. However, in many nuclear physics experiments and medical applications, diamond offers significant advantages due to its outstanding features, such as a near tissue equivalence, high radiation hardness and reliable operation in harsh environments. A monolithic ΔE–E diamond-based telescope was fabricated. The thicknesses of the two detection stages were 2.5 μm and 500 μm for the ΔE and E stage, respectively. The device was characterised by means of IBIC (Ion Beam Induced Charge) analysis at the Ruđer Bošković Institute ion microbeam. The detector, irradiated with different low energy ions ranging from helium to oxygen, showed good homogeneity of the response on a well-defined sensitive volume with a charge collection efficiency close to 100%. The ΔE stage showed a very good linear response on a wide range of LET values in diamond (170–3140 keV/μm). Due to its relatively low thickness, it can be successfully used as a microdosimeter. Time coincidence measurements have demonstrated the diamond telescope capability of discriminating and identifying the impinging ions. However, when the ratio between the energy deposited by the particle in the E stage and in the ΔE stage is small, the response of the E stage was observed to be affected by a cross-talk between the two stages of the device. A method to correct the E response for such effect was developed and successfully applied to the acquired data. Highlights: Development of a diamond-based ΔE-E telescope detector. Detector characterisation by means of IBIC analysis using different low energy ions. Thicknesses estimation by means of measurements at increasing tilt-angles. Proof of concept for its simultaneous use as microdosimeter/particle discriminator.